2015
DOI: 10.2334/josnusd.57.277
|View full text |Cite
|
Sign up to set email alerts
|

The use of lasers for direct pulp capping

Abstract: Direct pulp capping helps extend the life of a diseased tooth by maintaining tooth vitality. Nowadays, lasers are more frequently used during direct pulp capping in the clinic, but their use has not been previously reviewed. This review presents the basic properties of currently available lasers, scientific evidence on the effects of laser application on direct pulp capping, and future directions for this technology. An extensive literature search was conducted in various databases for articles published up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 94 publications
0
19
0
Order By: Relevance
“…The laser-irradiated pulp tissue exhibits various responses, which largely depend on irradiation settings such as wavelength, output power, waveform, pulse duration, interval time, focal spot size, energy density, total energy and others (2)(3)(4)(5)(6)(7)15,(20)(21)(22). Therefore, it is imperative to understand the precise specifications of laser devices when using a laser beam for treatments in the clinic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The laser-irradiated pulp tissue exhibits various responses, which largely depend on irradiation settings such as wavelength, output power, waveform, pulse duration, interval time, focal spot size, energy density, total energy and others (2)(3)(4)(5)(6)(7)15,(20)(21)(22). Therefore, it is imperative to understand the precise specifications of laser devices when using a laser beam for treatments in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, several methods and chemical agents have been evaluated for their effectiveness and pulp tissue cytotoxicity. Several studies have used laser irradiation for the management of exposed pulp tissue . A CO 2 laser emits infrared light with a wavelength of 10.6 μm, which is efficiently absorbed by water in vital tissues.…”
Section: Introductionmentioning
confidence: 99%
“…4 Moreover, a hydrokinetic system serves to minimize the mechanical damage to the structure of teeth without any thermal risk. [5][6] This photo-thermal interaction within tissue ablation produces a therapeutic effect by removing organic material and the smear layer, while also ensuring a decontaminated operation site.…”
Section: Introductionmentioning
confidence: 99%
“…Two types of MTA: White and Gray MTA The major difference between GMTA and WMTA are the presence of the higher amount of aluminum, magnesium, and iron in the former material. Because of potential discoloration effect of gray MTA, white MTA has been introduced into endodontic treatment.According to Ali Eskandarizadeh et al no significant difference was found between GMTA and WMTA in terms of calcified bridge thickness and pulp inflammatory response to the capping materials [17] VII. Niinuma A studied that the physical properties of MTYA1-Ca were significantly superior to those of Dycal.…”
Section: Lasersmentioning
confidence: 99%
“…In vitro and in vivo studies confirmed MTA's excellent sealing ability and biocompatibility. [17] According to M. Aeinehchi et al after six month follow up using MTA a 0.43 mm-thick dentine bridge and a nearly regular odontoblastic layer were noted. No inflammation, necrosis or calcifications were registered.…”
Section: Lasersmentioning
confidence: 99%